Corrosion Evaluation of SS-304 Stainless Steel for the Application to Heat Pumps - Arteaga,C. Cuevas (2005)
Studies of the corrosion evaluation of SS-304 stainless steel exposed in aqueous lithium bromide solution have been carried out applying the electrochemical noise technique, polarization curves and the weight loss method. The test temperatures were 50, 60 and 70 °C, and the exposure time was for fifteen days. The main objective was to determine the corrosion rates and the type of corrosion that SS-304 suffers under the mentioned conditions with the purpose of evaluating its application to heat pumps/transformers. The results showed that at the three test temperatures the type of corrosion was a mixed and pitting process. At 60 °C, it was observed some anodic peaks at the fifth day of exposure, indicating pitting nucleation. From 7 to 12 days a regular and continue pitting process was observed, and then the corrosion process became in generalized type. At 70 °C, some isolated and medium intensity peaks were observed, presenting behaviour of some mixed and pitting corrosion. The resistance noise was calculated through a statistical analysis, and then the Stern-Geary equation and Faraday Law were applied to determine the mass loss, which was compared to that obtained from weight loss method. Tafel slopes were determined from experimental polarization curves. To support the metallic oxidation carried out on the stainless steel surface, atomic absorption analysis was made to the solution corrosion products.